2016
DOI: 10.5296/ijl.v8i4.9725
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Locative and Directional Motion Events in English and Arabic

Abstract: This paper provides a contrastive analysis of locative and directional motion events in English and Arabic. Within a micro-parametric approach to crosslinguistic variation, it argues that both languages encode the distinction between manner and direction in their inventory of motion verbs. In the prepositional domain, purely locative and directional prepositions are shown to exist in the two languages; they respectively derive locative and directional interpretations with manner of motion verbs. The class of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In Persian and other languages, Motion verbs have been examined from different perspectives. In Persian, relevant research is found in Eslamipour and Sharafzadeh (2018), Rezaei and Diyanati (2017), Shahhoseini et al (2017), Akhavan et al (2017), Zeddari (2016), Mesgarkhooei (2014), Hamedi Shirvan and Sharifi (2013), Azkia (2012), Feizabadi and Pado (2012), Babai (2011), Golfam et al (2012) and Amouzadeh and Soltani (2011). In other languages, Verkerk (2015), Abdulrahim (2013), Lindesey (2011), Maalej (2011), Cifuentes-Ferez (2010 and Berthele (2004) are among the most outstanding works on motion verbs.…”
Section: Motion Event and Motion Verbsmentioning
confidence: 99%
“…In Persian and other languages, Motion verbs have been examined from different perspectives. In Persian, relevant research is found in Eslamipour and Sharafzadeh (2018), Rezaei and Diyanati (2017), Shahhoseini et al (2017), Akhavan et al (2017), Zeddari (2016), Mesgarkhooei (2014), Hamedi Shirvan and Sharifi (2013), Azkia (2012), Feizabadi and Pado (2012), Babai (2011), Golfam et al (2012) and Amouzadeh and Soltani (2011). In other languages, Verkerk (2015), Abdulrahim (2013), Lindesey (2011), Maalej (2011), Cifuentes-Ferez (2010 and Berthele (2004) are among the most outstanding works on motion verbs.…”
Section: Motion Event and Motion Verbsmentioning
confidence: 99%
“…Specificity is expressed by time adverbials. Relevant to the same function, fī preposition, referring to the place and time (Sibawayhi, 1988(Sibawayhi, [1975), and commonly known as a locative and temporal marker (Wright, 1996;Mehdi & Jaradat, 2021;Zeddari, 2016), strengthens the concrete signification.…”
Section: Interpretation Of Factormentioning
confidence: 99%
“…The work of Talmy and Slobin on motion events has motivated abundant research in different languages. Relevant Arabic research includes Saidi 2007;Al-Qarni 2010;Abdulrahim 2013;AlMurshidi 2013;Zeddari 2016;andAlhamdan, Alenazi, andMaalej 2018. Saidi (2007) studies motion events in Tunisian Arabic and concludes that it presents other strategies in the encoding of motion event other than those accounted for by Talmy's typology.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Al-Qarni (2010) and AlMurshidi (2013) do not question Talmy's typology, both concluding that Arabic is dominantly V-framed although some S-framed patterns are also used. Abdulrahim's (2013) and Zeddari (2016) focus on more specific phenomena within the topic of motion events. Abdulrahim's (2013) corpus-based study is limited to seven Arabic GO and COME verbs, but offers a comprehensive and empirically grounded treatment of these verbs by examining the contextual features that typically associate with each verb in actual usage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation